2013
DOI: 10.1016/j.brainres.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spines and associated terminals on brainstem neurons controlling auditory input

Abstract: Spines are unique cellular appendages that isolate synaptic input to neurons and play a role in synaptic plasticity. Using the electron microscope, we studied spines and their associated synaptic terminals on three groups of brainstem neurons: tensor tympani motoneurons, stapedius motoneurons, and medial olivocochlear neurons, all of which exert reflexive control of processes in the auditory periphery. These spines are generally simple in shape; they are infrequent and found on the somata as well as the dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…For tensor tympani injections (Billig et al 2007), there is early labeling of large neurons with long, radiating dendrites (although longer survival times yield a wider variety of neurons). These radiate multipolar cells, some of which have been reported to project to the opposite CN (Doucet and Ryugo 2006;Brown et al 2013b), were not labeled in the present studies. Stapedius injections of PRV yield a mixture of cell types in the CN, and labeling is seen at earlier times in the superior olivary complex (Windsor et al 2007;Mukerji et al 2010).…”
Section: Cochlear Nucleus Cell Types Providing Inputs To Oc Neuronscontrasting
confidence: 53%
See 1 more Smart Citation
“…For tensor tympani injections (Billig et al 2007), there is early labeling of large neurons with long, radiating dendrites (although longer survival times yield a wider variety of neurons). These radiate multipolar cells, some of which have been reported to project to the opposite CN (Doucet and Ryugo 2006;Brown et al 2013b), were not labeled in the present studies. Stapedius injections of PRV yield a mixture of cell types in the CN, and labeling is seen at earlier times in the superior olivary complex (Windsor et al 2007;Mukerji et al 2010).…”
Section: Cochlear Nucleus Cell Types Providing Inputs To Oc Neuronscontrasting
confidence: 53%
“…The few neurons located on the LSO margins (LOC "shell neurons," Vetter and Mugnaini 1992) were large (average 28.9×11.9 μm, SD 5.2×2.2 μm, for four neurons). Some MOC neurons and LOC shell neurons had dendrites with visible spines (Mulders and Robertson 2000b;Benson and Brown 2006;Brown et al 2013a). Axonal labeling was uncommon, but several cases had a few OC axons projecting dorsalward in the brainstem.…”
Section: Prv Labeling Of Oc Neuronsmentioning
confidence: 99%
“…In contrast to these excitatory synaptic inputs, we previously demonstrated that MOC neurons receive inhibitory synaptic inputs from neurons of the medial nucleus of the trapezoid body (MNTB), which can suppress spontaneous action potentials in MOC neurons in brain slice preparations in vitro (Torres Cadenas et al., 2020). MOC neurons may also receive additional synaptic inputs from brain regions involved in sound perception, as well as those involved in other roles such as attention (Brown et al., 2013; Caicedo & Herbert, 1993; Christian Brown et al., 2013; Faye‐Lund, 1986; Gómez‐Nieto, Horta‐Junior et al., 2008; Groff & Liberman, 2003; Horvath et al., 2003; Mulders & Robertson, 2002; Mulders et al., 2002; Ota et al., 2004; Suthakar & Ryugo, 2017; Thompson & Thompson, 1993; Vetter et al., 1993). How these various synaptic inputs integrate and impact MOC neuron activity remains an important unanswered question in auditory processing and cochlear gain control.…”
Section: Introductionmentioning
confidence: 99%